Especially vulnerable witnesses - Brkić Snežana S. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2014)
The subject of this article is the category of especially vulnerable witnesses in criminal procedure. The article is divided into sixth parts. The first part offers a review of various definitions of especially vulnerable witnesses in comparative law. The second focuses on the procedural protection of especially vulnerable witnesses in Serbian legislation. The third is concerned with the tactical rules of questioning of especially vulnerable witnesses. In the fourth part the author points to the importance of special services for providing assistance and support to especially vulnerable witnesses. The fifth part presents similarities and differences between protection of especially vulnerable witnesses and other forms of witness protection. The sixth part reflects on conclusions.